Development of chicks during extreme cold conditions: the Antarctic Petrel (Thalassoica antarctica) - Bech, Claus; Mehlum, Fridtjof; Haftorn, Svein (University of Ottawa Press, 1988)
Pages: 1447-1456 Publication Title: Acta XIX Congressus Internationalis Ornithologici Volume: 2 Place: Ottawa, Canada
Keywords: Dronning Maud Land; fugler; konferanse; kongress; ornitologi; zoologi

Navigation to nest site in the snow petrel (Pagodroma nivea) - Haftorn, Svein; Mehlum, Fridtjof; Bech, Claus (The Condor, 1988)
Publisher: American Ornithological Society
Keywords: Dronning Maud Land; NARE 1984/85; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Size variation in the snow petrel Pagodroma nivea - Haftorn, Svein; Mehlum, Fridtjof; Bech, Claus (Notornis, 1988)
Keywords: Dronning Maud Land; forskning; fugler; ornitologi; zoologi

Census of breeding Antarctic petrels Thalassoica antarctica and physical features of the breeding colony at Svarthamaren, Dronning Maud Land, with notes on breeding snow petrels Pagodroma nivea and south polar skuas Catharacta maccormicki - Mehlum, Fridtjof; Gjessing, Yngvar; Haftorn, Svein; Bech, Claus (Polar Research, 1988)
Keywords: Dronning Maud Land; NARE 1984/85; fugler; ornitologi; zoologi

Breeding ecology of the Antarctic petrel Thalassoica Antarctica in Mühlig-Hofmannfjella, Dronning Maud Land - Fridtjof, Mehlum; Claus, Bech; Svein, Haftorn (Proceedings of the NIPR Symposium on Polar Biology, 1987)
Keywords: Dronning Maud Land; NARE 1984/85; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Interrelationships between egg dimensions, pore numbers, incubation time, and adult body mass in Procellariiformes with special reference to the Antarctic petrel Thalassoica antarctica - Mehlum, Fridtjof; Rahn, Hermann; Bech, Claus; Haftorn, Svein (Polar Research, 1987)
Keywords: Dronning Maud Land; NARE 1984/85; ekspedisjoner; forskning; fugler; ornitologi; zoologi

A quantitative analysis of the behaviour of the Chinstrap penguin Pygoscelis antarctica and Macaroni penguin Eudyptes chrysolophus on Bouvetoya during the late incubation and early nestling periods - Haftorn, Svein (Polar Research, 1986)
Keywords: Bouvetøya; ekspedisjoner; pingviner; zoologi

Antarktis petrellen - verdens mest hardføre fugl? - Haftorn, Svein (Viten : populær vitenskap, 1986)
Keywords: Dronning Maud Land; forskning; fugler; ornitologi; zoologi

Fugler i de norske deler av Antarktis - Mehlum, Fridtjof (Vår fuglefauna, 1986)
Publisher: Norsk ornitologisk forening
Keywords: Bouvetøya; Dronning Maud Land; NARE 1984/85; Peter I. Øy; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Petreller i Dronning Maud Land - Mehlum, Fridtjof (Polarboken, 1986)
Publisher: Norsk Polarklubb
Keywords: Dronning Maud Land; NARE 1984/85; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Ecology of Cryptopygus sverdrupi (Insecta: Collembola) from Dronning Maud Land, Antarctica - Sømme, Lauritz (Polar Biology, 1986)
Observations on the ecology of Cryptopygus sverdrupi Lawrence (Collembola, Isotomidae) were made with specimens from the Mühlig-Hofmannfjella, Dronning Maud Land, Antarctica. At an elevation of 1600 m a.s.l. the species was numerous in association with the green alga Prasiola on gravel fields and in crevices of large boulders. The distribution of size-classes in field samples suggested that the population comprised several overlapping generations. Growth and development is probably very slow due to long winters and daily periods of subzero temperatures in their microhabitat during the summer. Specimens collected in mid-January had a mean supercooling point of-24.6°C with small individual variations. The lack of high supercooling points in the summer suggests that the springtails feed on a nuleatorfree diet. The ability to supercool was increased during prolonged starvation and acclimation at 0,-4 and-8°C. Glycerol and other potential low molecular weight cryoprotective substances were demonstrated in specimens acclimated at-4 and-8°C. The species possessed a relatively high tolerance to desiccation.
Keywords: Dronning Maud Land; entomologi; kuldetoleranse; leddyr; zoologi; økologi

New records of terrestrial arthropods from Dronning Maud Land, Antarctica - Sømme, Lauritz (Polar Research, 1986)
Keywords: Dronning Maud Land; ekspedisjoner; entomologi; forskning; leddyr; zoologi

Ornithological investigations in Mühlig-Hofmannfjella, Dronning Maud Land - Mehlum, Fridtjof; Bech, Claus; Haftorn, Svein (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Dronning Maud Land; NARE 1984/85; fugler; ornitologi; zoologi

Ecological studies on Cryptopygus sverdrupi from Muhlig-Hofmannfjella, Antarctica - Sømme, Lauritz (Cryo-Letters, 1985)
Keywords: Dronning Maud Land; entomologi; kuldetoleranse; leddyr; zoologi; økologi

Terrestrial invertebrates of Mühlig-Hofmannfjella, Dronning Maud Land - Sømme, Lauritz (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Dronning Maud Land; NARE 1984/85; leddyr; virvelløse dyr; zoologi

Insekter i Antarktis - Sømme, Lauritz (Forskningsnytt, 1983)
Keywords: Dronning Maud Land; ekspedisjoner; entomologi; forskning; insekter; zoologi

The Southern giant petrel Macronectes giganteus (Gmelin) on Bouvet Island - Haftorn, Svein; Voisin, Jean-Francois (Fauna Norvegica. Serie C. Cinclus, Norwegian Journal of Ornithology, 1982)
Keywords: Bouvetøya; forskning; fugler; ornitologi; zoologi

Studies of arthropod cold hardiness - Block, William; Sømme, Lauritz (British Antarctic Survey Bulletin, 1981)
Keywords: Antarktis; kuldetoleranse; leddyr; virvelløse dyr; zoologi

A census of penguins and seals on Bouvetøya - Haftorn, Svein; Sømme, Lauritz; Gray, John S (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; pingviner; seler; zoologi

Cold tolerance of alpine, Arctic, and Antarctic Collembola and mites - Sømme, Lauritz (Cryobiology, 1981)
Because of their dominant role in the fauna of alpine, Arctic and Antarctic locations Collembola and mites are of particular interest regarding adaptations to low temperatures. No freezing-tolerant species have been found in these groups of terrestrial arthropods, and it appears that all species depend entirely on supercooling to survive the lower temperatures of their habitats. While summer animals have high supercooling points, an increase in supercooling ability occurs during autumn and early winter, and can be explained as a two-step process. Initially gut content has to be eliminated to avoid heterogeneous nucleation at high subzero temperatures due to foreign nucleating agents. Second, supercooling is further enhanced through accumulation of glycerol or other lowmolecular cryoprotective substances. Further studies are needed on the ability of such animals to avoid inoculative freezing in their microhabitats.
Keywords: Antarktis; entomologi; kuldetoleranse; midder; miter; virvelløse dyr; zoologi

Supercooling in two Antarctic arthropods from Bouvetøya - Sømme, Lauritz (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; kuldetoleranse; leddyr; virvelløse dyr; zoologi

A note on Norwegian observations of whales in the Antarctic - Fevolden, Svein Erik (Report of the International Whaling Commission, 1980)
Keywords: Sørishavet; hvaler; zoologi

Terrestrial arthropods from Vestfjella, Dronning Maud Land (Acari, Collembola), with notes on their taxonomy - Sømme, Lauritz (Insect Systematics & Evolution, 1980)
Keywords: Dronning Maud Land; ekspedisjoner; entomologi; forskning; leddyr; zoologi

Fra et opphold på Bouvetøya i 1979 - Vinje, Torgny E (Polarboken, 1980)
Keywords: Bouvetøya; ekspedisjoner; zoologi